COMBINATION OF THE PROFILE MATCHING AND TOPSIS METHOD IN DECISION SUPPORT SYSTEM OF LECTURER PERFORMANCE ASSESSMENT - I Putu Dody Suarnatha; I Gede Aris Gunadi (Jurnal Riset Informatika, 2021)
An information system is a system within an organization that collects data management needs, supports operations, has important management and strategy in organizational or institutional activities, and provides reports to certain parties by using computers as a means to access the internet. To be able to manage data in the form of a database, it is necessary to develop a web-based information system. For that we need an information system that can facilitate the sale of a sales transaction and as a promotional event, so that it is expected to improve the company and compete with other companies. Public relations can be interpreted as relations between publics, indicating that there are many publics who have to do these relationships, and because there are many publics, it means that there are many relationships. The purpose of making this web program is to facilitate service sales transactions so that they are more efficient, fast and easy without the need to be hindered by distance and time.